MARKETING AND SALES STRATEGY DEVELOPMENT FOR NEW SEASONING PRODUCT (A CASE STUDY: PASS BUMBU SERBAGUNA) - siti nurfitriana (IULI Publisher, 2022)
PASS Bumbu Serbaguna is the latest portfolio from Kriya Mandiri Restu, a MSME producing food raw materials. PASS Bumbu Serbaguna is consists of a mixture of spices, which is used for enhancing the flavor of foods, such as rendang, gulai, fried rice, aceh noodles, satay, tongseng, or even middle eastern food. The potential B2B market of PASS Bumbu Serbaguna is relatively large but the company has limited resources. So, the company must create a strategy to sell the product to the most potential food merchant or called the beachhead market, to obtain an effective and efficient sales process. Therefore, this research is aimed to determine the beachhead market and marketing strategy that is proposed in accordance to the marketing mix. The steps follow the framework from Bill Aulet, on his book